The Huntress a novel - Quinn, Kate; Maarleveld, Saskia (New York HarperCollins, 2019)
A fascinating historical novel about a battle-haunted English journalist and a Russian female bomber pilot who join forces to track the Huntress, a Nazi war criminal gone to ground in America.
Compact discs.
Performed by Saskia Maarleveld.
107317
Keywords: Nazi hunters -- Fiction; Women air pilots -- Fiction; Journalists -- Fiction; Women war criminals -- Fiction; War -- Psychological aspects -- Fiction; War victims -- Fiction; Historical -- Fiction -- General; War & Military. -- Fiction; Espionage -- Fiction -- Thrillers; Audiobooks; Fiction; Historical fiction